Các NGUY CƠ đỐi vỚi SỨC KHỎE cỦa dân CƯ NÔNG THÔN do Ảnh hưỞng cỦa DIOXIN NỒNG ĐỘ THẤP Ở CÁC VÙNG BỊ RẢI CHẤT HỦY DIỆT SINH THÁI/dioxin - V.S., Rumac; N.V., Umnova; D.A., Belov; К.А., Turbabina; G.А., Sofronov; Ngô, Thanh Nam; Vũ, Thị Loan; Võ, Viết Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
HEALTH RISKS CAUSED BY EXPOSURE TO LOW DIOXIN CONCENTRATIONS OF THE RURAL INHABITANTS LIVING IN THE ECOCIDE SPRAYED TERRITORIESThe present reviewed the ecological toxicology and the epidemiologic studies to assess the long-term biomedical consequences of exposure to low dioxin concentrations of the rural inhabitants living in the ecocide sprayed areas. It was hypothesied that the kinetic and dynamic properties of the low dioxin concentrations caused the development of dioxin pathology. The results showed that the relatively low levels of toxicPCDD/PCDF congeners were found in the soil and fish samples. However, small quantities of these substances might be accumulated in the human bodies during ontogenesis, primarily transferred by transplacental and lactational routes, and with food. The emphasis on results of health risks was the exposure to trace-level dioxins in the early stages of life. The effects of such exposure on health and development of children, health of adult population were evaluated. Further studies should be done to establish the pathological mechanisms of dioxins in animal models.